Analisis Yuridis Pemberantasan Perdagangan Manusia Di Indonesia Dan Vietnam - Siti Nurjanah; Boy Ericson Siahaan (Fakultas Hukum, Universitas Internasional Batam, 2015)
This research report has has the aim to determine the effort and the application of penalties in combating human trafficking crime committed by Indonesia as a country that ratified the Palermo Protocol 2000 on human trafficking and Vietnam as countries that ratified the UN Convention on Transnational Crime Organized (TOC) and the acceding the 2000 Palermo Protocol and to know how the application of criminal penalties for human trafficking in Indonesia and Vietnam. The UN also classifies the states according to the high level of human trafficking into the SYSTEM ( TIER ) is a Tier 1 , Tier 2 Watch List, and Tier 3 in order to be able to do oversight and the classification is based on the standards of the Trafficking Victims Protocol Act of 2000 (TVPA 2000). Methodology conducted by the author is doing normative legal research or research library where library materials constitute the basic data in (science) research classified as secondary data using juridical approach and data analysis in this research is descriptive qualitative.Indonesia has legislations and has made many efforts both bilaterally and multiteral with many countries in combating trafficking and has established various organizations in suppressing and combating trafficking in persons and Vietnam also has special regulations regarding to human trafficking, and effective start from early 2012, but still Penalty Code that determines the punishment of suspect and Vietnam have been doing international cooperation both in bilateral and Multiteral in combating trafficking in persons.